2020
DOI: 10.1016/j.ajem.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of small-bore tube thoracostomy (≤20 Fr) for chest trauma patients: A retrospective observational study

Abstract: Introduction: Tube thoracostomy is an important treatment for traumatic hemothorax and pneumothorax. The optimal tube diameter remains unclear. To reduce invasiveness, we use small-bore chest tubes (≤20 Fr) for all trauma patients for whom tube thoracostomy is indicated in our emergency department (ED). The aim of this study was to investigate the effectiveness and safety of small-bore tube thoracostomy for traumatic hemothorax or pneumothorax. Method: We conducted a retrospective observational study at a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, the present-day literature focuses on the less invasive techniques in the management of traumatic or spontaneous pneumothorax [7][8][9][10]. Kulvatunyou et al [11], in a randomized clinical trial, showed that there is no difference in clinical outcomes comparing PC versus CT in patients with traumatic pneumothorax, with benefit in pain relief in patients with PC, with the lesser failure rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present-day literature focuses on the less invasive techniques in the management of traumatic or spontaneous pneumothorax [7][8][9][10]. Kulvatunyou et al [11], in a randomized clinical trial, showed that there is no difference in clinical outcomes comparing PC versus CT in patients with traumatic pneumothorax, with benefit in pain relief in patients with PC, with the lesser failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…The use of less invasive techniques is increasing, such as the utilization of PC in the management of pneumothorax. Multiple studies [7][8][9][10] are now evaluating the advantages and benefits of this approach; Bauman et al [5] show that in terms of failure rates there is no difference between CT and PC, with a better patient's experience, comparable results with Kulvatunyou et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies reported that a single chest tube inserted through the incision may not be favorable for the drainage of blood, even if using the conventional 26‐Fr chest tube. 10 Maezawa et al 25 demonstrated that an 8 Fr pigtail catheter may achieve a similar effect in treating traumatic hemothorax when compared to a 20 Fr chest tube. In this study, postoperative persistent bleeding in the chest was not encountered in any patient, and we plan to observe the drainage effect of a 12‐Fr pigtail catheter in case of postoperative bleeding in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent guidelines from the American College of Surgeons Advanced Trauma Life Support (ATLS) recommend using smaller (28-32 Fr) chest tubes to treat pneumothorax [ 8 ]. However, smaller tubes, including pigtail catheters, may be equally effective [ 12 ]. Tension pneumothorax requires immediate decompression.…”
Section: Discussionmentioning
confidence: 99%